Morphology-dependent electrocatalytic nitrogen reduction on Ag triangular nanoplates. Issue 72 (20th August 2019) - Gao, Wen-Yan; Hao, Yu-Chen; Su, Xin; Chen, Li-Wei; Bu, Tong-An; Zhang, Nan; Yu, Zi-Long; Zhu, Zhejiaji; Yin, An-Xiang
Abstract : Ag triangle-nanoplates and potassium cations can synergistically promote electrocatalytic nitrogen fixation in aqueous solutions under ambient conditions. Abstract : Electrocatalytic nitrogen reduction reactions (ENRR) can produce ammonia from nitrogen and water under ambient conditions. Here, we report the morphology-dependent electro-catalytic nitrogen reduction on Ag triangular nanoplates. Boosted by potassium cations, Ag triangular nanoplates with sharp edges exhibit a high faradaic efficiency of 25% with an ammonia yield of 58.5 mg gAg −1 h −1 at a low overpotential of −0.25 V vs. RHE. In comparison, rounded Ag nanoparticles mainly enclosed by 111 and 100 surfaces show a much smaller faradaic efficiency of 16% and ammonia yield of 38 mg gAg −1 h −1 at a larger overpotential (−0.35 V vs. RHE).